2014
DOI: 10.1097/qai.0000000000000299
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an Education and Home-Based Pedometer Walking Program on Ischemic Heart Disease Risk Factors in People Infected with HIV

Abstract: An education and home-based pedometer walking program improves physical activity levels, and beneficial changes in other IHD risk factors were noted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
128
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 59 publications
(128 citation statements)
references
References 44 publications
0
128
0
Order By: Relevance
“…In these four studies, all quality of life domains either stayed the same or improved in participants exposed to the HBR interventions, while the level of perceived stress in the intervention group was inversely associated with interaction over the six-month period of the prescribed walking programme in the Roos et al (2014) study. These improvements in psychological parameters following a period of HBR mirror the reported psychological benefits of exercise in previous systematic reviews on the effects of resistance, aerobic and concurrent exercise training for PLHIV.…”
Section: Effectiveness Of Hbr Interventions On Quality Of Life and Pamentioning
confidence: 86%
See 4 more Smart Citations
“…In these four studies, all quality of life domains either stayed the same or improved in participants exposed to the HBR interventions, while the level of perceived stress in the intervention group was inversely associated with interaction over the six-month period of the prescribed walking programme in the Roos et al (2014) study. These improvements in psychological parameters following a period of HBR mirror the reported psychological benefits of exercise in previous systematic reviews on the effects of resistance, aerobic and concurrent exercise training for PLHIV.…”
Section: Effectiveness Of Hbr Interventions On Quality Of Life and Pamentioning
confidence: 86%
“…The only validated outcome measure used in the Maharaj and Chetty (2011) study was the SF-36, which demonstrated a significant improvement in all quality of life (QoL) domains among the participants in the intervention group. The fourth of the RCT studies (Roos et al 2014), demonstrated significant between-group effects in a six-minute walk test distance, waist to hip ratio, as well as glucose and high-density lipoprotein levels over a 12-month period. Drop-out rates ranged from 5% to 38% for these four studies and were higher in the control groups than in the intervention groups.…”
Section: Individual Study Outcomesmentioning
confidence: 95%
See 3 more Smart Citations